Body composition differences by age and playing standard in male rugby union and rugby league: A systematic review and meta-analysis - Geeson-Brown, T.; Jones, B.; Till, K.; Chantler, S.; Deighton, K. (Journal of Sports Sciences, 2020)
This systematic review and meta-analysis aimed to determine differences in body compositionn between playing standard and age in male rugby union and rugby league athletes. The MOOSE (Meta-analysis of Observational Studies in Epidemiology) guidelines for design, implementation, and reporting were followed. Studies were required to be in male rugby union or league and have body composition as the primary or secondary outcome. Data was required to be presented separately for positional groups and body composition presented as whole-body. A systematic search was performed in PubMed, Cochrane Library, MEDLINE, SPORTDiscus, and CINHAHL via EBSCOhost. 57 studies were included for meta-analysis. Results highlighted significantly higher fat-free mass in senior elite than senior sub-elite or junior elite athletes for all RU and RL forwards. Small and non-significant differences were found in fat mass between rugby union playing standards and age categories. Rugby league senior elite forwards had less fat mass than junior elite forwards. Practitioners should prioritise training and nutritional strategies that maximise fat-free mass development, especially in junior elite cohorts.